The Influence of Current Ratio and Debt to Equity Ratio on Net Profit Margin: Study On One of The Health Service and Hospital Provider Companies for The Period 2018-2022 - Rohayati Nursita; Maulana Yusup; Adam Ramdani; Galih Putra Prawiranegara (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study examines the impact of the Current Ratio and debt-to-equity ratio on the net profit Margin of a health service and hospital provider, Tbk, throughout the specified period. Financial ratios are crucial for evaluating a company's financial health, particularly in the healthcare sector, necessitating substantial spending in operational management and facility growth. The Current Ratio indicates the company's capacity to fulfill short-term liabilities, whereas the debt-equity ratio assesses the debt-to-equity ratio within the capital framework. The employed research approach is the classical assumption test, which verifies the regression model's precision utilized to examine the relationship between the independent and dependent variables. The classical assumption test encompasses normality, heteroscedasticity, multicollinearity, and autocorrelation tests to verify that the model is unbiased and yields valid results. The study's findings reveal that the Equity Ratio exerts a considerable negative impact on the Nett Profit Margin, indicating that an increased proportion of debt relative to equity results in a heightened financial burden for the organization. This condition adversely affects profitability, as the company must devote most of its income to meet financial obligations. Conversely, a more balanced capital structure management can enhance net income and the company's financial well-being. This discovery has significance for the management of Tbk enterprises in developing more effective financial strategies, particularly in regulating debt and equity levels to avoid adversely affecting profitability. Companies must implement measures to diminish reliance on external financing and enhance operational efficiency to bolster competitiveness in the healthcare sector. Furthermore, optimizing asset utilization and diversifying revenue streams may serve as strategies to enhance profitability sustainably. This study underscores the significance of equilibrium in the financial framework to guarantee sustained long-term growth. By effectively managing financial ratios, a healthcare and hospital service provider can enhance financial stability and sustain higher profitability in confronting future business issues.